Uses of growth mindset in the teaching profession: A Systematic Literature Review - Taveras, Carmen Maura; Santelices Etchegaray, María Verónica (Revista Complutense de Educación, 2025)
INTRODUCTION. Growth mindset – the belief that abilities and intelligence are malleable – is mostly studied for students, there is little research regarding of the uses of this kind of beliefs for teachers. This systematic review of literature provides a state of the art of empirical studies whose main unit of analysis are teachers. METHODS. By doing a thorough search in the Web of Science, Scopus, and Scielo databases, we find a total of 90 articles and select 29 both qualitative and quantitative studies who gather our inclusion and exclusion criteria. RESULTS. Our results report that there is mostly positive evidence regarding the uses of growth mindset in three areas of the teaching profession: wellness or wellbeing, pedagogical practices, and the possibilities to change teacher beliefs. However, we find little to no evidence regarding the uses of growth mindset in hazardous phenomena for teachers such as low retention rates. DISCUSSION. The uses of growth mindset in students exceeds the use that this same mindset has in teachers to improve multiple educational indicators, like performance in students’ standardized tests and persistence of students towards the achievement of their academic and personal goals. Thus, it is important to promote the use of this kind of mindset to try to solve serious problems of low teacher retention, especially when teachers are expected to promote this type of beliefs in their students. Our review includes limitations and recommendations for future research.
Keywords: growth mindset; implicit theories of intelligence; teaching profession; teachers' beliefs